PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN MAHASISWA KULIAH PADA STIE PASAMAN - M Saleh Lubis (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
The Higher Educational Institution plays an important role to generate the high quality of Human Resources on Indonesia. Application of the professional marketing management on this institution is important too. Among the important aspects of marketing management is the words of mouth by the students were satisfied. This study examines the impact of service quality and customer value on satisfaction of students study at STIE Pasaman. Number of sampel is 241 people drawn by Slovin formula from 604 population. The results of this study showed the quality of service and customer value of each partial positive and significant impact on student satisfaction study at STIE Pasaman. The results of this study imply that in order to improve the satisfaction of students studying at STIE Pasaman can be done by increasing again service quality and customer value. Key words : Satisfaction, service quality and customer value.